ISOTOPIC EVIDENCE FOR PALAEOTEMPERATURES AND DEPTH STRATIFICATION OF MIDDLE CRETACEOUS PLANKTONIC FORAMINIFERA FROM THE PACIFIC OCEAN - Price G.D.; Sellwood B.W.; Corfield R.M.; Cartlidge J.E. (My University, 1998)
Stable isotopic measurements have been made on both planktonic foraminifera and coccolithic matrix of Middle Cretaceous (Late Albian-Cenomanian) age from two Pacific low latitude sites. The degree of alteration of the foraminifera has been assessed through the application of chemical analyses, cathodoluminescence and Scanning Electron Microscopy (SEM). The rotaliporid foraminifera display an interspecies range of δ18O values from -2.29 to -3.01‰ at Deep Sea Drilling Project (DSDP) Site 463 and from -2.74 to -3.55‰ at DSDP Site 305. Hedbergellid foraminifera exhibit a δ18O interspecies variation of -2.52 to -3.02‰ at Site 305. Isotopic analysis of individual Hedbergella delrioensis and Rotalipora appenninica foraminifera from single samples shows H. delrioensis to have a surprisingly large spread of δ18O values (-2.492 to -3.097‰ from Site 463, -2.454 to -3.344‰ from Site 305), whilst δ13C values remain confined to a narrower range. Such a spread of oxygen values may be related to a number of factors, including subtle diagenetic alteration, a wide range of temperature-related depth habitats or growth related changes of primary skeletal calcite. The hedbergellids have consistently lighter oxygen and heavier carbon isotopic values than do the rotaliporid foraminifera and hence provide isotopically derived palaeotemperatures consistent with a thermally stratified ocean. At both sites the oxygen isotopic data are consistent with a gradual warming through Albian-Cenomanian time. However, the results suggest that Middle Cretaceous equatorial oceans were possibly only as warm as those of the present day (or slightly warmer), but did not reach the high temperatures claimed in older literature.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая